Flexible polypyrrole-coated conductive fabric sensor for large deformation measurement. Issue 5 (27th June 2019) - Zhang, Chi; Xue, Pu; Luo, Yubo
Abstract : Purpose: Strain sensors have been widely used to measure the strain of the structure. However, the ordinary sensing elements are not suitable for measuring large deformation on an irregular surface, which limits their applications. Recently, flexible sensors have attracted extensive interest because they can overcome the shortage of the ordinary sensing elements. The paper aims to discuss this issue. Design/methodology/approach: In this paper, the whole measurement process of strain sensing behavior and the dimension design of fle3xible strain sensing system use the macroscopic measurement method of material tensile test to accurately measure the resistance change with strain. Afterwards, combining electrical components, the flexible strain sensors are produced for two biomedical applications: the wearable data-collecting gloves and rehabilitation training system. Findings: The results show that the developed conductive fabric can exhibit high sensitivity, large workable strain range (>50 percent) under simple and repeated tension and good stability. Both applications demonstrate that the polypyrrole-coated fabric sensor can successfully measure the large and repeat strain, capture the motion of body and display corresponding information almost in real time. Originality/value: The limitation lies in the lack of a holistic strain sensing mechanism study, and the lack of a corresponding theoretical model to explain the experimental results.